Modular Low-Power, High-Speed CMOS Analog-to-Digital Converter for Embedded Systems - Lin, Keh-La. (The International Series in Engineering and Computer Science, Analog Circuits and Signal Processing, 2003)
One of the main trends of microelectronics is toward design for integrated systems, i.e., system-on-a-chip (SoC) or system-on-silicon (SoS). Due to this development, design techniques for mixed-signal circuits become more important than before. Among other devices, analog-to-digital and digital-to-analog converters are the two bridges between the analog and the digital worlds. Besides, low-power design technique is one of the main issues for embedded systems, especially for hand-held applications. Modular Low-Power, High-Speed CMOS Analog-to-Digital Converter for Embedded Systems aims at design techniques for low-power, high-speed analog-to-digital converter processed by the standard CMOS technology. Additionally this book covers physical integration issues of A/D converter integrated in SoC, i.e., substrate crosstalk and reference voltage network design.